Chaos parameters for EEG analysis - Ulbikas, J.; Čenys, A.; Sulimova, O. P. (Nonlinear Analysis: Modelling and Control, 1998)
The possibility to apply nonlinear dynamics methods for the EEG time series analysis is investigated. Problems related with the estimation of the chaos parameters from the physiological data are discussed.
Keywords: none